(untitled) (Research, Society and Development, 2025)
Introduction: The clinical and therapeutic interactions between atrial fibrillation and chronic kidney disease have become a relevant object of study in the medical context, given the high incidence of the diseases coexisting in the same patient. Objective: The aim of this study was to characterize the clinical and therapeutic interactions between atrial fibrillation and chronic kidney disease, building on robust literature reviews. Materials and Methods: This is an integrative literature review on the congruences between clinical and therapeutic aspects of atrial fibrillation and chronic kidney disease. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Atrial Fibrillation”; “Chronic Kidney Disease”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The studies showed that there is a bidirectionality in the clinical and therapeutic interactions between atrial fibrillation and chronic kidney disease. In this sense, the mechanisms of cardiac structural remodeling and systemic inflammation stand out as the cause of this coexistence and cause-effect, resulting in clinical manifestations and the need for new propaedeutics Conclusion: It is necessary to consider the degree of renal dysfunction when establishing the treatment of atrial fibrillation in patients with chronic kidney disease, in order to avoid an increase in complications and cardiovascular risk.